Synchronous pleomorphic adenoma and oncocytic carcinoma in the ipsilateral parotid gland. Issue 7 (September 2018) - Lee, D.H.; Choi, Y.D.; Yoon, T.M.; Lee, J.K.; Lim, S.C.
Abstract: Synchronous benign and malignant tumours in the ipsilateral parotid gland are rare. We present a case of pleomorphic adenoma and oncocytic carcinoma in the same parotid gland. Clinicians should be aware of the possibility of such synchronous multiple tumours, and that careful dissection and palpation during operation are important to diagnose them.